Design, analysis and performance evaluation of inerter-based linear and nonlinear vibration suppression systems - Dong, Zhuang (2021)
The inerter is a recently proposed passive mechanical element, which can be used to provide inertial coupling to modify the behaviour of dynamic systems. Since its introduction, it has been used to improve the performance of vibration mitigation systems such as automobile shock absorbers and building vibration control systems. However, the effects of the addition of the inerter on vibration characteristics of dynamical systems have not been fully discovered. This thesis aims to propose and evaluate different inerter-based vibration suppression systems, to investigate the effects of adding the linear and nonlinear inerters on their dynamical performance in terms of force transmission and energy transmission, and to provide a better understanding of the inerter-based vibration suppression systems. Two inerter-based linear vibration suppression systems are proposed. The vibration power flow behaviour and performance of the inerter-based vibration isolators mounted on finite and infinite beam structures are investigated. It is demonstrated that the addition of the inerter can suppress the vibration substantially in terms of power transmission. The wave dissipation and damping properties of continuous metamaterial beam structures with embedded inerter-based devices are investigated. Different inerter-based configurations are proposed and evaluated in terms of frequency response functions and structural damping. It is shown that exceptional energy dissipation properties are obtained when the proposed inerter-based oscillators are employed to support a continuous beam structure. Coupled systems with nonlinear inerter-based devices are investigated to evaluate the performance in terms of vibration suppression. By configuring a pair of oblique inerters, a nonlinear inertance mechanism is created and used in nonlinear inerter-based nonlinear isolator and nonlinear joint. It is demonstrated that the addition of the nonlinear inertance mechanism within the nonlinear isolator twists the peak of response amplitude curve to lower frequencies and reduces the response amplitude. The power transmission is also reduced within a specific frequency range. By placing the nonlinear-inerter joint at different positions, the response amplitudes associated with the out-of-phase mode and in-phase mode can be significantly reduced and the force transmission and power transmission can be substantially reduced at prescribed frequencies. The work described in this thesis provides new designs and insights into the dynamics and performance of inerter-based vibration suppression systems. Both the linear and nonlinear vibration suppression systems are investigated and evaluated in terms of response amplitude, force transmissibility and power transmission. The findings facilitate more reliable and effective designs of inerter-based vibration suppression systems with improved dynamic performance. These studies yield in-depth understanding of the effects of inerter-based devices on vibration attenuation and benefit further designs for better vibration suppression systems employing inerters.